2017
DOI: 10.1111/zph.12392
|View full text |Cite
|
Sign up to set email alerts
|

Re‐emergence of rabies virus maintained by canid populations in Paraguay

Abstract: Paraguay has registered no human cases of rabies since 2004, and the last case in dogs, reported in 2009, was due to a variant maintained in the common vampire bat "Desmodus rotundus". In 2014, a dog was diagnosed as positive for rabies with aggression towards a boy and all required measures of control were successfully adopted. Epidemiological investigation revealed that the dog was not vaccinated and had been attacked by a crab-eating fox, "zorro" (Cerdocyon thous). The sample was diagnosed by the Official V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Rabies virus circulates through two different epidemiological cycles: terrestrial and bat-borne, associated with different species within the orders Carnivora and Chiroptera, respectively. In Argentina, two terrestrial variants are found: V1 associated with domestic dogs; V2 circulates among sylvatic canids, particularly in the crab-eating fox, Cerdocyon thous [10,11]. Argentinian bat-borne variants can be subdivided into two groups: those circulating among insectivorous bats and variants associated with the hematophagous bat Desmodus rotundus.…”
Section: Introductionmentioning
confidence: 99%
“…Rabies virus circulates through two different epidemiological cycles: terrestrial and bat-borne, associated with different species within the orders Carnivora and Chiroptera, respectively. In Argentina, two terrestrial variants are found: V1 associated with domestic dogs; V2 circulates among sylvatic canids, particularly in the crab-eating fox, Cerdocyon thous [10,11]. Argentinian bat-borne variants can be subdivided into two groups: those circulating among insectivorous bats and variants associated with the hematophagous bat Desmodus rotundus.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic resurgences of rabies have occurred around the world in recent times, including Paraguay (Amarilla et al 2018), New York, USA (Chang et al 2002), and KwaZulu-Natal Province in South Africa (Weyer 2018). According to the World Health Organization (WHO), 95% of rabies cases reported annually are from Africa and South East Asia alone, with disadvantaged communities being particularly vulnerable (WHO 2019).…”
Section: Vultures and The Prevention Of Diseasementioning
confidence: 99%
“…Essas estimativas temporais (2004 e 2014) marcam um período de exclusão praticamente total da raiva, não somente no nosso país, mas também em países vizinhos, como o Paraguai. 28 Ao longo do nosso estudo o que chama mais a atenção é que tanto em nosso país, como em diversos outros países houve um longo tempo sem casos notificados de raiva, seja ela animal ou humana o que levou a uma redução massiva em relação a vacinação dos cães levando dessa forma a falsa percepção, por parte da população, de que a vacina não seria mais importante para a manutenção do quadro epidemiológico vigente. Outra hipótese que estaria levando a essa redução seria decorrente de um problema registrado com lotes da vacina em 2010, culminando assim na morte de dezenas de animais em todo o Brasil, o que fez com que a aderência de cães e gatos sofresse uma queda, conforme afirma a Organização Mundial de Proteção Animal.…”
Section: Ministério Da Saúde (Brunclassified